How do hospital providers perceive and experience the information-delivery process? A qualitative exploratory study - Cristiana Fortini; Jean-Bernard Daeppen (Elsevier, 2023)
Objective: To explore how professionals deal with informing their patients and how they experience the process per se, in order to deepen understanding of the issues involved and to identify areas of focus for improvement. Methods: Semi-structured qualitative interviews were conducted with 13 hospital professionals at Lausanne University Hospital, Switzerland. Results: Information includes feedback, practical information, patient condition, treatment/process of care, and educational material. Information-delivery is a process that involves informing the patient then checking patient reception of the information. The main expected outcome is patient action. Providers can feel trapped, guilty, inadequate, powerless, disenchanted when the process fails to achieve its expected purpose. Conclusions: Informing and checking strategies are not implemented optimally, and providers could benefit from guidance in order to decrease discomfort and become more proficient at delivering information. Innovation: Addressing the information-delivery process per se provides us with a novel insight into the complexity of the process and contributes to identifying essential ingredients of future innovative training programs for providers at large.